Administrasi Guru: Upaya Peningkatan Kualitas Profesionalisme Mengajar - Syahmidi Syahmidi; Surawan Surawan (Departement of Mathematics Education, 2022)
The purpose of this article is that teacher professionalism is measured from administrative completeness in the process of planning and implementing learning. Because teacher professionalism is needed in the world of education in Indonesia, because this will be one measure of the success of the world of education. This research is descriptive qualitative in nature with 4 Fiqh teachers at MA Muslimat NU as the subject, Palangka Raya City. The results of this study show that 95.78% of teachers strongly agree regarding administrative completeness and 4.22% agree. The planning made jointly by teachers at MA Muslimat NU already includes various components that have been determined in the 2013 Curriculum such as school identity, subjects, class/semester, subject matter, time allocation, learning objectives, KD, indicators of achievement of competence, learning methods, media, tools, learning resources, steps of learning activities and assessment. All these components are packaged in one RPP.